PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA OUTSOURCING DI INDONESIA - Julianti, Lis (Jurnal Advokasi, 2015)
The outsourcing system is a reasonable business policies of a company in thecontext of business efficiency. Outsourcing arrangements according to Employment Law inÂ Indonesia in regulated at Article 64 of Act 13 of 2003 on Employment. However, workerswho perform work in the outsourcing company should not lose their rights areconstitutionally protected. Implementation of outsourcing, within a few years after thepublication of Act 13 of 2003 on Employment still have many weaknesses; mainly this isdue to the lack of regulations issued by the Government as well as inequities in theimplementation of the employment relationship between the employer and the worker.